3D modeling of geosynthetic-reinforced pile-supported embankment under cyclic loading. Issue 2 (7th August 2019) - Pham, H. V.; Dias, D.; Dudchenko, A.
Abstract : Geosynthetic-reinforced pile-supported (GRPS) embankments are an attractive soft soil improvement technique. They are broadly used in infrastructure projects. Most previous studies focused on investigating reinforced piled embankments under static loading. There is a paucity of studies on structure behavior under cyclic loading. In the study, three-dimensional numerical modeling using the finite element method (FEM) was performed with the objective of better understanding the cyclic behavior of GRPS embankments in terms of load transfer mechanisms and settlements. An advanced constitutive model based on the hypoplasticity concept was employed for the embankment fill to simulate the cumulative strain during each loading cycle. Parametric studies related to the embankment height, traffic loading parameters (amplitude and frequency), and number of geosynthetic reinforcement layers are presented. The numerical results obtained indicate that the presence of a geosynthetic reinforcement decelerates the reduction in the arching effect within the embankment fill and decreases the cumulative settlements. The rate of the cumulative settlements decreases with the number of load cycles. The number of geosynthetic reinforcement layers does not appear to influence the soil arching and cumulative settlements.